Multiparametric spectral problems as expanded by the author’s own vectors - Berezansky Yu. М.; Konstantinov , A. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We prove the expansion theorems for abstract multiparameter spectral problems. These theorems contain expansion results for general operators with continuous spectrum and partial differential elliptic operators.